The Wellbeing and Vulnerability of Child Labor in Urban Slum Areas of Cirebon: a Study of Photovoice Narrative - Hidayat, Ade; Mutaqin, Zaenal; Isnaeni, Nur (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
This study aims to explore the welfare and vulnerability of child laborers in urban slums in Cirebon City, a topic that has often been overlooked in previous studies. Using a narrative photovoice approach, six participants aged 10–17 years were involved as the main subjects to document their life experiences through photographs. Key findings indicate that child laborers face various multidimensional vulnerabilities, including physical health, psychosocial, economic, and educational challenges, exacerbated by inadequate living conditions, hazardous work, and limited educational access. On the other hand, they also demonstrate significant resilience and survival strategies. Data analysis based on triangulation of narratives, visual materials, and in-depth interviews reveals the need for a comprehensive approach to addressing this issue, including improvements in social policy, community empowerment, and increased public awareness. This study contributes to a new understanding of the subjective experiences of child laborers and its relevance in developing evidence-based policies. [Penelitian ini bertujuan mengeksplorasi kesejahteraan dan kerentanan pekerja anak di kawasan kumuh perkotaan Kota Cirebon, suatu topik yang seringkali kurang dieksplorasi dalam penelitian sebelumnya. Melalui pendekatan naratif photovoice dengan melibatkan enam partisipan berusia 10-17 tahun sebagai subjek utama untuk mendokumentasikan pengalaman hidup mereka menggunakan foto. Temuan utama menunjukkan bahwa pekerja anak menghadapi berbagai kerentanan multidimensi, termasuk kesehatan fisik, psikososial, ekonomi, dan pendidikan, yang diperburuk oleh kondisi tempat tinggal tidak layak, pekerjaan berisiko, dan akses pendidikan yang terbatas. Di sisi lain, mereka juga menunjukkan ketahanan dan strategi bertahan hidup yang signifikan. Analisis data berbasis triangulasi narasi, visual, dan wawancara mendalam mengungkapkan perlunya pendekatan komprehensif untuk mengatasi masalah ini, mencakup perbaikan kebijakan sosial, pemberdayaan komunitas, dan peningkatan kesadaran publik. Penelitian ini berkontribusi pada pemahaman baru tentang pengalaman subjektif pekerja anak dan relevansinya dalam menyusun kebijakan berbasis bukti].